ANDRAGOGI YANG HUMANIS - Retno Widyaningrum (Perspektif Ilmu Pendidikan, 2007)
Teaching is principally based on pedagogi and andragogi. Pedagogi is normally used to teach young learners, while andragogi is used for adults. However in practice pedagogi which tends to transfer knowledge and make passive learning is often used for adults. This article discusses how andragogi can be used to make teaching human and how to humanize learners by using andragogi. It is believed that andragogi can create active learning in which the learners can meet their needs such as esteem and self actualization. Discussing humanistic andragogi from different views this article concludes its importance and advantages in life long learning and provides some suggestion how to carry out humanistic andragogi for active, creative,innovative and joyfull learning.